Minis, Memsahibs and the Plantation Past: Tracing Gendered Histories and Colonial Violence in Arupa Patangia Kalita’s Josnar Jhitas - Diganta Deka (HISTORICAL: Journal of History and Social Sciences, 2025)
Arupa Patangia Kalita’s Josnar Jhitas (2022) is a significant intervention in the literary reconstruction of gendered histories silenced by dominant colonial narratives. The novel is set against the historical backdrop of British colonial expansion and the rise of Assam’s tea industry. It focuses on the character Durgi Bhumij, an immigrant tea plantation worker and freedom fighter, whose experiences in Atharighat tea estate reveal the complex interplay of gender, class and colonial oppression. While mainstream historiography often erases the lives and resistances of women from the margins, Kalita’s narrative counters this trend by restoring the agency of characters like Durgi, who actively participated in anti-colonial efforts, including the boycott of British goods and engagement in the freedom movement. The novel offers a fictional but historically grounded portrayal of how women like Durgi navigated their lives amidst love, displacement, violence, and a sense of patriotism within the confines of colonial plantation capitalism. Situating the novel within postcolonial feminist discourse and subaltern historiography, the paper explores how Kalita reimagines history through fiction, rendering visible the otherwise erased narratives of gendered violence and anti-colonial resistance. The plantation, depicted as a space of exploitation and transformation, becomes the ground where Durgi asserts moral and political sovereignty, culminating in her participation in the Swadeshi movement and her martyrdom. The paper argues that Kalita’s novel both recuperates the nuanced gendered experiences of the colonial period and subverts dominant historiographical narratives.